THE EFFECTS OF GYMNASTICS TRAINING ON FLEXIBILITY AND STRENGTH IN CHILDREN - Ömer ÖZER; Recep Soslu; Erhan Devrilmez; Osman Uyhan; Meltem Devrilmez; Ismail Dogan (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
The aim of this study was to examine the effects of gymnastics training on flexibility and strength parameters of gymnasts. A total of 48 boys aged 5-7 years participated in this study voluntarily. Participants were randomly assigned to two groups (Experimental group n=24; age, height, weight and BMI 6.21±1.10 years, 114.18±19.98 cm, 22.38±4.09 kg, 15.85±1.59 kg/m², respectively; Control group n=24; age, height, weight and BMI (6.87±0.74 years, 114.18±19.98 cm, 22.38±4.09 kg, 15.90±2.72 kg/m², respectively). Standing Long Jump test (SLJ), Bent Arm Hang (BAH), Sit Ups in 30seconds Cruch (SUC), Sit and Reach Flexibility Test (SRF) and Static Flexibility (SF) tests were applied to the experimental and control groups. The training was applied to the experimental group three days a week for 12 weeks, each time for the duration of 90 minutes. A two-way Repeated Measure ANOVA (2×2) was used to test for interactions and main effects for time (pre-test vs. post-test) and group (experimental vs. control) on the dependent physical performance variables. Results showed that there was a statistically significant difference in the TSC and SR values of the experimental group from pre to post-tests (p<0.01, d=0.95, p<0.01, d=0.75, respectively). There were no significant differences in other parameters. According to post-test group difference results, experimental group participants performed better than those in the control group in terms of BAH, SUC, SLJ and SRF values (p<0.02, d=0.780; p<0.04, d=0.614; p<0.00, d=2.11 respectively). As a conclusion, gymnastic training program significantly improved strength and flexibility of gymnasts aged 5-7 years.